1999
DOI: 10.1038/sj.onc.1202944
|View full text |Cite
|
Sign up to set email alerts
|

The APC protein binds to A/T rich DNA sequences

Abstract: The tumor suppressor protein APC (Adenomatous Polyposis Coli) is localized in the cytosol and in the nucleus. In this study, we demonstrate that the nuclear APC protein level is high in cells in the basal crypt region of the normal colorectal epithelium. Strikingly, the APC protein staining resembles the staining pattern of a nuclear proliferation marker. As a ®rst step towards a possible role of the nuclear APC protein, we provide data showing the direct interaction of the nuclear APC protein with DNA. A nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 26 publications
0
35
0
1
Order By: Relevance
“…Adenomatous polyposis coli has been shown to interact with DNA (Deka et al, 1999), leading to the possibility that interaction with the Ku heterodimer may have occurred indirectly through DNA molecules with double-strand breaks. To eliminate this possibility, the IP was repeated in the presence of DNase.…”
Section: Resultsmentioning
confidence: 99%
“…Adenomatous polyposis coli has been shown to interact with DNA (Deka et al, 1999), leading to the possibility that interaction with the Ku heterodimer may have occurred indirectly through DNA molecules with double-strand breaks. To eliminate this possibility, the IP was repeated in the presence of DNase.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its modular organization, PTP-BL may build up a multiprotein complex recruiting the APC protein within the nucleus, which may be involved in cell cycle regulation. Thus, overexpression of the APC protein blocks the progression from G0 ± G1 to the S phase of the cell cycle Ishidate et al, 2000) and the capability of the APC protein to interact directly with DNA was demonstrated recently (Deka et al, 1999). Although these data suggest an involvement of the APC protein in cell division, the intracellular signaling cascades involved in APC function remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…19). In fact, in both cells and tissue, smaller APC isoforms shown by immunoblot were recognized by antibodies directed against both N-and C-terminal portions of the protein (12,20). In addition, several known splice forms do eliminate exon 1 (21), which might explain the failure of Nterminal antibodies to detect expression in this instance.…”
Section: Discussionmentioning
confidence: 99%
“…APC expression at lateral cell borders and near apical membranes in mouse and human tissue has been reported (7-10). Nuclear APC was first characterized in tissue culture cells (6), but has also been reported in mouse and human colon tissue (11,12). The subcellular localization of APC thus reflects its function as a regulator of ␤-catenin.…”
Section: Discussionmentioning
confidence: 99%